Preparation and Characterization of Edible Straw Made from Dragon Fruit Peel to Solve The Problem of Plastic Waste - Darmawan, Melissa Salma; Daeni, Fitri; Kurniawan, Tessa Surya; Listiaji, Prasetyo (Universitas Negeri Semarang, 2022)
Plastic waste is a global environmental problem that is being faced by the world, especially Indonesia. In addition, Indonesia is ranked 4th in producing plastic straw waste. This problem needs to be taken seriously because the waste generated through plastic straws is difficult to recycle. One effort that can be done is to replace plastic straws with edible straws. Red dragon fruit peel contains nutrients such as carbohydrates, fat, protein, and dietary fiber but is often only thrown away and considered as waste. This study aims to utilize dragon fruit peel as a basic material for making edible straws and to analyze the characteristics of edible straws. The study used quantitative experimental methods by testing temperature resistance and water absorption. The results showed that edible straw has good temperature resistance at a temperature of 10℃-20℃, where at that temperature there is an increase in mass of about 2-3 grams. As for water absorption, a good temperature range is 20℃-80℃ where absorption occurs between 0.38%-7.46%.